Antimicrobial activities of Cassia sophera L. extract - Aziz, S; Sorowar, M S; Parveen, S; Satter Miah, MA; Siddique, S; Ara Begum, MH (Bangladesh Journal of Scientific and Industrial Research, 2023)
This study investigates the antibacterial activities of a variety of extracts from several parts of Cassia sophera L. which include the stem, leaf, flower, and seed from n-hexane, chloroform, ethyl acetate, and methanol extract. The disc diffusion method, at a concentration of 300 μg/disc, was employed to test the extracts against several pathogenic microorganisms. Some of the extracts were antibacterial against the bacteria tested, with inhibition zones ranging from 7.0 to 25.0 mm in diameter. In comparison to a streptomycin standard sample, the organic extracts showed almost identical activity in a few cases. The ethyl acetate extract of the seed had the highest activity against Sarcina sp. and Pseudomonas aeruginosa, with inhibition zones of 25.0 mm and 23.0 mm in diameter, respectively. Methanol extract of the flower was most effective against Bacillus cereus (inhibition zone of 18.0 mm), while chloroform extract of the leaf was most effective against Bacillus cereus (inhibition zone of 18.5 mm). The result of present research is expressing the high potency of various parts of the plant extracts to stop the growth of bacteria and this extract can be further suggested for medical utilization and could be used as natural antimicrobial source. Bangladesh J. Sci. Ind. Res. 58(1), 45-52, 2023